Brain-targeted intranasal delivery of dopamine with borneol and lactoferrin co-modified nanoparticles for treating Parkinson's disease. (1st January 2019) - Tang, Shengnan; Wang, Aiping; Yan, Xiuju; Chu, Liuxiang; Yang, Xiucheng; Song, Yina; Sun, Kaoxiang; Yu, Xin; Liu, Rongxia; Wu, Zimei; Xue, Peng
Abstract: Efficient delivery of brain-targeted drugs is highly important for successful therapy in Parkinson's disease (PD). This study was designed to formulate borneol and lactoferrin co-modified nanoparticles (Lf-BNPs) encapsulated dopamine as a novel drug delivery system to achieve maximum therapeutic efficacy and reduce side effects for PD. Dopamine Lf-BNPs were prepared using the double emulsion solvent evaporation method and evaluated for physicochemical and pharmaceutical properties. In vitro cytotoxicity studies indicated that treatment with dopamine Lf-BNPs has relatively low cytotoxicity in SH-SY5Y and 16HBE cells. Qualitative and quantitative cellular uptake experiments indicated that Lf modification of NPs increased cellular uptake of SH-SY5Y cells and 16HBE cells, and borneol modification can promote the cellular uptake of 16HBE. In vivo pharmacokinetic studies indicated that AUC0–12 h in the rat brain for dopamine Lf-BNPs was significantly higher ( p  < .05) than that of dopamine nanoparticles. Intranasal administration of dopamine Lf-BNPs effectively alleviated the 6-hydroxydopamine-induced striatum lesion in rats as indicated by the contralateral rotation behavior test and results for striatal monoamine neurotransmitter content detection. Taken together, intranasal administration of dopamine Lf-BNPs may be an effective drug delivery system for Parkinson's disease.